Sticking With It: ER-PM Membrane Contact Sites as a Coordinating Nexus for Regulating Lipids and Proteins at the Cell Cortex - Zaman, Mohammad F.; Nenadic, Aleksa; Radojičić, Ana; Rosado, Abel; Beh, Christopher T. (Frontiers in Cell and Developmental Biology, 2020)
Membrane contact sites between the cortical endoplasmic reticulum (ER) and the plasma membrane (PM) provide a direct conduit for small molecule transfer and signaling between the two largest membranes of the cell. Contact is established through ER integral membrane proteins that physically tether the two membranes together, though the general mechanism is remarkably non-specific given the diversity of different tethering proteins. Primary tethers including VAMP-associated proteins (VAPs), Anoctamin/TMEM16/Ist2p homologs, and extended synaptotagmins (E-Syts), are largely conserved in most eukaryotes and are both necessary and sufficient for establishing ER-PM association. In addition, other species-specific ER-PM tether proteins impart unique functional attributes to both membranes at the cell cortex. This review distils recent functional and structural findings about conserved and species-specific tethers that form ER-PM contact sites, with an emphasis on their roles in the coordinate regulation of lipid metabolism, cellular structure, and responses to membrane stress.